Epibulbar Osseous Choristoma: a Clinicopathological Case Series and Review of the Literature - Vachette, M.; Moulin, A.; Zografos, L.; Schalenbourg, A. (Klinische Monatsblätter für Augenheilkunde, 2012)
Background: Choristomas are benign, congenital tumours composed of normal tissue in an abnormal location. Osseous choristomas represent the rarest form of epibulbar choristomas, with now 65 cases reported in the literature. We did a retrospective clinicopathological study of all patients with epibulbar osseous choristoma observed at our institution since 1982 and updated the last review of the literature.History and Signs: Three Caucasian male patients, aged between 3 months and 11 years, were identified. All osseous choristomas were located under the superotemporal bulbar conjunctiva of the right eye.Therapy and Outcome: All lesions were managed with surgical excision. Histopathology revealed the presence of lamellar bone in all cases, one of which was associated with a dermolipoma.Conclusions: We report a small rare case series of 3 epibulbar osseous choristomas and did a review of the literature. In one patient, the osteoma was associated with a dermolipoma, corresponding to the fourth reported complex choristoma of this type, in an otherwise normal eye, in the literature.
Keywords: osteoma; choristoma; dermolipoma; epibulbar; bone and bones